Pembentukan Peradilan Khusus Penyelesaian Hasil Pemilihan Kepala Daerah dalam Pelaksanaan Pemilu Serentak Nasional - Mohammad Syaiful Aris (Universitas Airlangga, 2022)
AbstractThe urgency of establishing a special court for resolving election disputes because this special court is an order of Law Number 8 of 2015 which must be formed before the implementation of the national simultaneous regional elections in 2024. Although, in its development, The Constitutional Court Decision Number 85/PUU-XX/2022, the Constitutional Court has the authority to examine and adjudicate cases of disputes over election results are no longer limited to “until the establishment of a special judicial body”, but will be permanent, because such a special judicial body will no longer be formed. However, this is considered less than ideal. This study aims to outline the urgency of a special judiciary for the resolution of regional head election results in the implementation of national simultaneous elections using conceptual and statutory approaches. The results showed that it is necessary to establish a special judicial model for national simultaneous elections, which is a special judiciary that is ad hoc under the general judicial environment of the Supreme Court. For the seat of the special judiciary for dispute resolution, the regional elections are placed on the High Court to resolve disputes over the results of elections in the province as is the model of the corruption court based in the provincial capital so that the budget for the establishment and management of this special judiciary is not too large. Keywords: Election; Election Law; Special Courts for Regional Head Elections. AbstrakUrgensi pembentukan peradilan khusus penyelesaian sengketa pilkada karena peradilan khusus ini merupakan perintah Undang-Undang Nomor 8 Tahun 2015 yang harus dibentuk sebelum pelaksanaan Pilkada serentak nasional tahun 2024. Walaupun, dalam perkembangannya Putusan MK Nomor 85/PUU-XX/2022, Mahkamah Konstitusi berwenang memeriksa dan mengadili perkara perselisihan hasil pemilihan tidak lagi terbatas hanya “sampai dibentuknya badan peradilan khusus”, melainkan akan bersifat permanen, karena badan peradilan khusus demikian tidak lagi akan dibentuk. Tetapi, hal tersebut dirasa kurang ideal. Penelitian ini bertujuan untuk menguraikan urgensi peradilan khusus penyelesaian hasil pemilihan kepala daerah dalam pelaksanaan pemilu serentak nasional dengan menggunakan pendekatan konseptual dan perundang-undangan. Hasil penelitian menunjukkan bahwa perlu dibentuk suatu model peradilan khusus untuk pemilu serentak nasional, yang merupakan sebuah Peradilan khusus yang bersifat ad hoc di bawah lingkungan peradilan umum pada Mahkamah Agung. Untuk tempat kedudukan Peradilan khusus penyelesaian sengketa Pilkada diletakan pada Peradilan Tinggi untuk menyelesaikan sengketa hasil pilkada di wilayah propinsi tersebut sebagaimana model pengadilan tindak pidana korupsi yang berkedudukan di ibukota propinsi sehingga anggaran untuk pendirian dan pengelolaan peradilan khusus ini tidak terlalu besar. Kata Kunci: Pemilu; Hukum Pemilu; Peradilan Khusus Hasil Pemilihan Kepala Daerah.